Cardiorespiratory Coordination During Exercise in Adults With Down Syndrome - Oviedo, Guillermo R.; Garcia-Retortillo, Sergi; Carbó-Carreté, María; Guerra-Balic, Myriam; Balagué, Natàlia; Javierre, Casimiro; Guàrdia-Olmos, Joan (Frontiers in Physiology, 2021)
Introduction: Down syndrome (DS) is a chromosomal disorder affecting simultaneously cardiovascular and respiratory systems. There is no research studying the coupling between these systems during cardiorespiratory exercise testing in a population with DS. Cardiorespiratory coordination (CRC), evaluated through principal component analysis (PCA), measures the covariation of cardiorespiratory variables during exercise. Objective: To investigate and compare CRC in adults with and without DS during maximal cardiorespiratory exercise testing. Methods: Fifteen adults with DS and 15 adults without disabilities performed a maximal cardiorespiratory exercise test on a treadmill. First, the slope, and afterward the velocity was increased regularly until participants reached exhaustion. The time series of six selected cardiorespiratory variables [ventilation per minute, an expired fraction of O2, the expired fraction of CO2, heart rate, systolic blood pressure (SBP), and diastolic blood pressure (DBP)] were extracted for the analysis. The number of principal components (PCs), the first PC eigenvalues (PC1), and the information entropy were computed for each group (non-DS and DS) and compared using a t-test or a Mann-Whitney U test. Results: Two PCs in the non-DS group and three PCs in the DS group captured the variance of the studied cardiorespiratory variables. The formation of an additional PC in the DS group was the result of the shift of SBP and DBP from the PC1 cluster of variables. Eigenvalues of PC1 were higher in the non-DS (U = 30; p = 0.02; d = 1.47) than in the DS group, and the entropy measure was higher in the DS compared with the non-DS group (U = 37.5; p = 0.008; d = 0.70). Conclusion: Adults with Down syndrome showed higher CRC dimensionality and a higher entropy measure than participants without disabilities. Both findings point toward a lower efficiency of the cardiorespiratory function during exercise in participants with DS. CRC appears as an alternative measure to investigate the cardiorespiratory function and its response to exercise in the DS population.